1993
DOI: 10.1063/1.354022
|View full text |Cite
|
Sign up to set email alerts
|

Modeling inactive boron during predeposition processes

Abstract: A new type of boron cluster is presented through the study of boron diffusion at high concentrations under predeposition conditions. Recent experimental results of boron predeposition give the opportunity to analyze, with the simulations, the behavior of the inactive part of the boron profile, found to increase dramatically with surface concentrations. After a rapid thermal annealing, the electrical activation appears to be extremely high due to the dissolution of the inactive part of the profile. The only way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…18,20,45 Then in 1999, there appeared simultaneously two DFT-based reports that led to an explicit debate regarding the dominant mechanism. Windl et al 49 used two variants of the nudged elastic band method (NEBM) in concert with a monopole correction for charged systems to obtain barriers between 39 and 68 kJ/mol (0.4 and 0.7 eV) for pair diffusion.…”
Section: History Of the Questionmentioning
confidence: 98%
“…18,20,45 Then in 1999, there appeared simultaneously two DFT-based reports that led to an explicit debate regarding the dominant mechanism. Windl et al 49 used two variants of the nudged elastic band method (NEBM) in concert with a monopole correction for charged systems to obtain barriers between 39 and 68 kJ/mol (0.4 and 0.7 eV) for pair diffusion.…”
Section: History Of the Questionmentioning
confidence: 98%
“…Based on a kinetic model, Vandenbossche and Baccus [11] showed that including a mobile and inactive substitutional-interstitial boron cluster B s -B i gave the best agreement with the experimental results of Inada et al [12]. However, based on ab initio density functional theory (DFT) studies Zhu et al [5] claimed that ''B s -B i is (relatively) immobile; it is impossible to find a migration path that only breaks one or two bonds while still keeping two B atoms together.''…”
mentioning
confidence: 99%
“…where the factor of 2 arises since two boron atoms are In addition to Vandenbossche and Baccus's work [11], the role of B s -B i diffusion can also be inferred from the observation of anomalous shouldering in diffusion profiles [9]. Clearly, such behavior cannot be explained by B s -Si i diffusion alone.…”
mentioning
confidence: 99%
“…10 Attempts have been made to reproduce an evolution of boron profiles under such experimental environments, with low concentration of self-interstitials using a kinetic Monte Carlo approach. 11 The main conclusion of that work was that neither boron-interstitial diffusion mechanism nor boron-interstitial plus boron clustering mechanisms can provide a good fit to experiment. Reasonable fit is only possible if mobile boron pairs are introduced into the model.…”
mentioning
confidence: 91%
“…Reasonable fit is only possible if mobile boron pairs are introduced into the model. 11 In response, Hwang et al used ab initio calculations to demonstrate that the ͗100͘ pair of interstitial and substitutional borons (B 2 I pair of Tarnow 12 ͒ can be mobile with intermediate energy barriers below 1 eV and total energy barrier of 1.8 eV. 13 However, the magnitude of this barrier ͑in comparison to other barriers for boron diffusion͒ could well render the assumption of immobility of the B 2 I pair to be fairly reasonable.…”
mentioning
confidence: 98%